2018
DOI: 10.18632/oncotarget.25285
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized analogs of Di(1H-indol-3-yl)methyl-4-substituted benzenes are NR4A1-dependent UPR inducers with potent and safe anti-cancer activity

Abstract: Di(1H-indol-3-yl)(4-trifluoromethylphenyl)methane (DIM-Ph-4-CF3) is an analog of orphan nuclear receptor 4A1 (NR4A1) ligand cytosporone B. We have synthesized several oxidation products of DIM-Ph-4-CF3, focusing on analogs with electron-withdrawing or donating groups at their phenyl ring 4-positions, and examined their anti-cancer activity and mechanism-of-action. Mesylates (DIM-Ph-4-X+ OMs–s) having CF3, CO2Me and Cl groups were more effective inhibitors of cancer cell viability than their precursors. 19F NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…This response was blocked by leptomycin B, a nuclear export inhibitor, and it was shown that AHPN-induced apoptosis was due to nuclear export of NR4A1 and mitochondrial targeting of the receptor (111). Similar effects were observed in cancer cells treated with many other structurally diverse compounds including phobol esters, etoposide, cadmium, cholic acid derivatives, etoposide, HDAC inhibitors, dibutyltin derivatives, coumarin analogues, bile acids, oxidized analogues of bis-indole derived compounds, acetylshikonin analogues, and n-butylenephthalide and related compounds (111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124). Many of these agents not only induced nuclear export and apoptosis in cancer cells but also increased overall levels of NR4A1.…”
Section: Extranuclear Nr4a Actionmentioning
confidence: 73%
“…This response was blocked by leptomycin B, a nuclear export inhibitor, and it was shown that AHPN-induced apoptosis was due to nuclear export of NR4A1 and mitochondrial targeting of the receptor (111). Similar effects were observed in cancer cells treated with many other structurally diverse compounds including phobol esters, etoposide, cadmium, cholic acid derivatives, etoposide, HDAC inhibitors, dibutyltin derivatives, coumarin analogues, bile acids, oxidized analogues of bis-indole derived compounds, acetylshikonin analogues, and n-butylenephthalide and related compounds (111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124). Many of these agents not only induced nuclear export and apoptosis in cancer cells but also increased overall levels of NR4A1.…”
Section: Extranuclear Nr4a Actionmentioning
confidence: 73%
“…The experiment was performed blindly in triplicates with positive and negative controls to ensure reproducibility. 25 26 27 …”
Section: Methodsmentioning
confidence: 99%